Peningkatan Kedisiplinan Siswa terhadap Prestasi Mata Pelajaran Akidah Akhlak Kelas X SMK PGII 2 Bandung - Irma Fadilah (UNISBA Press, 2022)
Abstract. Discipline is a step that makes students successful in carrying out their learning in school. Therefore, it is able to influence the success of students in their learning achievements. So, in carrying out discipline, there needs to be planning, implementation, and evaluation in carrying it out in order to be able to apply discipline properly and on target. So, based on this, researchers conducted research on